Implementations of The Digital Madrasah: Case Study on MTSN 1 Makassar - Muh Yamin; Dian Sanuri (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The demands of the times demand the world of education to be able to adapt and use technological developments in an effort to improve the quality of learning. The current development of information technology provides its own challenges in the world of education especially madrasah. Basically, the madrasah is an important Islamic educational institution in Indonesia, where its existence has proven to have marked a generation of nations with deep religious insights and the soul of nationalism. Therefore, the educational institutions of the Madrasah must be able to adapt to such massive technological developments. The madrasas must be capable of utilizing and integrating technology in teaching activities so that it becomes relevant and contextual with the development of the times. The aim of this research is to take stock of the efforts made by MTsN 1 Makassar in transforming into a digital madrasah, to find out the supporting factors and obstacles in implementing the digital madrasah policy. This type of research is qualitative descriptive. The results of the research describe the efforts made at MTsN 1 Makassar in transforming into a digital madrasah starting from the planning stage of both activity planning and budget planning, strengthening the quality of SDM by forming the learning revolution team 4. Supporting factors are the large number of digital flatforms that are open access, the support of the parents of the students and the factors that hinder are the price of relatively expensive digital devices, large electricity bills and a less stable internet network.